The Ornament in John Ruskin's thought (Palíndromo, 2020)
This paper aims to show and perceive the presence of the living ornament in the formation of John Ruskin's aesthetic thought. His reflections on the expressive work in architecture, manifested above all in its ornamentation, will be taken under the concept of the fantastic paradox of imperfection, which highlights the vitality and pleasure of the worker in his workshop practice. This manifestation of life and happiness could only be achieved by the communion between the manual and intellectual work of its artisans.
Keywords: John Ruskin; Architecture; Ornament; Imperfection